Synopsis of Chinese Alloperla Banks, 1906 (Plecoptera, Chloroperlidae), with description of a new species - Abdur Rehman; Qing-Bo Huo; Yu-Zhou Du (ZooKeys, 2025)
A new species of the genus Alloperla Banks, 1906 (Plecoptera, Chloroperlidae), Alloperla triquetra Rehman, Huo & Du, sp. nov., is described from Liaoning Province, China, with diagnostic features and color images of the adult habitus included. The terminalia of the new species are compared with those of related species, and key similarities and distinguishing characteristics are highlighted. In addition, the male of A. joosti Zwick, 1972 is described from China for the first time, as previous records included only females. Detailed color photographs of the dorsal and ventral views of the epiproct are provided, addressing a gap in the literature where illustrations of the ventral view were previously lacking a critical feature for accurate species identification. Furthermore, color illustrations and supplementary redescriptions of A. mediata (Navás 1925) and A. teleckojensis Šámal, 1939 from Liaoning Province, China are presented. An updated checklist and identification key to males of Chinese Alloperla species are also provided.